Grid Integrated Wind Energy Storage System for Linear and non-Linear Loads - Suresh, Dr. K.; Babu, A. R. Vijay; Venkatesh, P. M. (International Journal of Engineering and Technology, 2018)
The proposed system also has boost converter, bidirectional DC-DC converter and inverter for grid and wind energy integration. The boost inverter/buck rectifier in this system is controlled by ANFIS controller is for better output, boost and bidirectional DC-DC converters are controlled by PID controller in closed loop. Overall operations are based on modes main controller speedgoat, which is control the system operation in different modes. Any variation happening in the input, storage and load parameters speedgoat changing the mode and operate the system is in effective way. This paper presents harnessing of maximum wind energy from natural resource whenever it’s available. The power electronic converters role is important In between sources and load. The load may be linear and non-linear in nature, so converters performance decides the efficiency of the system. Proper controller can switch the converter in the desired time and improve the system performance and stability. Many controllers are suggests to control the converter to get better performance in at output side.